PAMAM dendrimers of generation 4.5 loaded with curcumin interfere with α-synuclein aggregation - Daniela E. Igartúa; Florencia González-Lizárraga; Carolina S. Martinez; Silvia del V. Alonso; César L. Ávila; Rosana Chehín; Nadia S. Chiaramoni; M. Jimena Prieto (Elsevier, 2023)
Curcumin (CUR) is a bioactive compound that has been proposed for the treatment of various neurodegenerative diseases. However, its use is limited due to its low solubility in aqueous media and chemical instability under physiological conditions. Herein, we propose a strategy to overcome these limitations by using PAMAM dendrimers of generation 4.5 (DG4.5). Using a combination of biophysical techniques together with in vitro models, we demonstrate that CUR-DG4.5 complexes: (i) increased the solubility and stability of CUR via internalization into dendrimer's pockets and interaction with terminal carboxylic groups; (ii) showed in vitro biocompatibility and increased CUR uptake; (iii) presented DPPH radical scavenging activity and in vitro inhibition of H2O2-induced stress; and (iv) interfere with α-synuclein aggregation. In conclusion, this work lays the foundation to use curcumin-loaded PAMAM dendrimers of generation 4.5 as nanodrugs capable of reducing oxidative stress and inhibiting α-synuclein aggregation to treat synucleinopathies.